The Role Of Parents In Meeting The Basic Physical Needs (Love, Nurture, Hone) Of Children With Down Syndrome In Tunge Village - Dodik Arso Wibowo; Wahyu Tanoto (Journal of Applied Nursing and Health, 2022)
Background: Down syndrome is the retardation of physical and mental growth caused by the developmental abnormalities of chromosome 21 that impact physical and mental barriers that experience the barriers of intellectual development and difficulty in adapting to the environment in everyday life. Children with Down syndrome have distinctive acceptable motor characteristics and other characteristics based on the degree of obstacles it has, which are coarse-hand fingers, stiff, weak muscles, emotional conditions that are difficult to guess and poorly restrained, dependence on adults, and often reject others. The research aims to know the parents' role in fulfilling the basic needs of physical (love, nurture, hone) of children with Down syndrome in Tunge village. Methods: The design of this study uses descriptive, a research population of 16 respondents, and a large sample of 16 respondents with the technique of "total sampling." This research was conducted  using a single variable, that is, the role of the parent in fulfillment of basic physical needs (love, nurture, hone) in children with Down Syndrome in village T with instruments in the form of questionnaires then the data is analyzed with percentage and interpreted quantitatively Results: The results of the study gained that of 16 respondents, half respondents had a good role, eight respondents (50%), nearly half of the respondents had a sufficient role of 7 respondents (44%), and a small fraction of the respondents had a less than one respondent (6%). Conclusion: It is influenced by several factors namely age, gender, occupation, last education. The results of this study are expected that parents can improve their role in fulfilling the physical basic needs (love, nurture, hone) in children with Down syndrome, and add insight in the process of fulfilling basic physical needs (love, nurture, hone)